Strategic or Piecemeal? Smart City Initiatives in Sydney and Melbourne. Issue 4 (2nd October 2019) - Dowling, Robyn; McGuirk, Pauline; Gillon, Charles
ABSTRACT: This paper focuses on the smart urbanism that is being crafted by local authorities in metropolitan Sydney and Melbourne, Australia. Offering an extensive analysis of the Australian context, we chart firstly how engagement with smart is primarily focused on improving quotidian local government functions. Second, our analysis of the diverse mechanisms and policies through which cities are being made smart shows that piecemeal initiatives rather than smart city strategies predominate in the two cities. There is a variegated geography of smart urbanism in these two cities, we conclude, that is incrementally rather than radically transforming cities and their governance. 本文着重考察澳大利亚悉尼和墨尔本市政府建设智能城市的努力。作者分析了澳大利亚的整体状况，进而指出政府的智 能化建设主要着眼于改善地方政府的日常功能。随后分析了建设智能城市的各种机制和政策，指出悉尼和墨尔本都采用 了积少成多的策略，而不是一步到位地建设。最后文章指出这两个城市及其治理的智能化如同星星之火，而不是激进的转化。